Application of Direct Instruction Model for Improving Learning Outcomes Biotechnology - Huda, Hisbulloh (Kamil : Journal of Education, 2025)
This study aims to analyze the effectiveness of implementing the Direct Instruction model in improving student learning outcomes on the topic of Biotechnology among grade IX B students at MTsN 4 Jombang in the 2025 academic year. The research employed a Classroom Action Research (CAR) design conducted through two learning cycles. Each cycle consisted of four stages: planning, acting, observing, and reflecting. The participants were 30 male students. Data were collected through observation and achievement tests administered at each cycle. The findings revealed that the average student score increased from 69.71 in Cycle I to 87.43 in Cycle II, with the percentage of mastery learning rising from 69.71% to 81.88%. This improvement indicates that the Direct Instruction model effectively enhanced the quality of learning, particularly in strengthening students’ conceptual understanding of biotechnology. These results affirm that systematic and consistent application of Direct Instruction can serve as an effective pedagogical alternative for teachers seeking to optimize science learning outcomes at the junior high school level